Optimization of the activity of Mo7-Zn3/CaO catalyst in the transesterification of waste cooking oil into sustainable biodiesel via response surface methodology - Kouider Elouahed, Salima; Asikin-Mijan, N.; Alsultan G., Abdulkareem; Kaddour, Omar; Yusop, M.R.; Mimoun, Hadj; Samidin, Salma; Mansir, Nasar; Taufiq-Yap, Y.H. (Elsevier, 2024)
An enriched basic site CaO-supported bimetallic Molybdenum-Zinc (Mo7-Zn3) catalyst was successfully synthesized via wet-impregnation and evaluated for the transesterification of waste cooking oil into biodiesel. The physicochemical characterization of the Mo7-Zn3/CaO catalyst demonstrated good dispersion of CaMoO4 and ZnO oxides on CaO support, with a mesoporous structure allowing for better mass transfer between reactants. The Mo7-Zn3/CaO catalyst exhibited high transesterification activity (95 ± 0.3 FAME conversion), owing to the large density of strong Brønsted basic sites (conjugated O2–) generated from simultaneous interaction among Ca2+, Zn2+ and Mo6+ metal species. Response Surface Methodology (RSM) and Box Behnken Design (BBD) were used to optimize the reaction and indeed, the utmost FAME conversion of 95 is achieved using 3.37 wt catalyst loading, 12:1 methanol to oil molar ratio within 2.27 h at 62.7 °C reaction temperature. The model reliability in predicting the FAME yield using the established catalyst under varying operational conditions was excitedly validated with a reasonable accuracy error of 0.5 . The catalyst exhibited good stability, maintaining a high FAME conversion (95–85 ) during 5 reusable cycles without significant loss in catalytic activity. A closer look for a detailed approach and a heterogeneous mechanism for the reaction using Mo7-Zn3/CaO catalyst was proposed. The physical and chemical properties of the produced biodiesel were carefully compared with the standard for biodiesel, and were found to majorly comply with ASTM D6751 and EN 14214 biodiesel properties. An investigation into the economic competitiveness and industrial applicability of biodiesel production using Mo7-Zn3/CaO from WCO reveals significant potential for sustainable and efficient biodiesel synthesis.